2005
DOI: 10.1086/428602
|View full text |Cite
|
Sign up to set email alerts
|

The Decay of Accreting Triple Systems as Brown Dwarf Formation Scenario

Abstract: We investigate the dynamical decay of non-hierarchical accreting triple systems and its implications on the ejection model as Brown Dwarf formation scenario. A modified chain-regularization scheme is used to integrate the equations of motion, that also allows for mass changes over time as well as for momentum transfer from the accreted gas mass onto the bodies. We integrate an ensemble of triple systems within a certain volume with different accretion rates, assuming several prescriptions of how momentum is tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 56 publications
9
89
0
Order By: Relevance
“…These distributions were truncated at a = 10 au in order to better match what is known about wider binary systems. We also trialled the prediction from a triple-body decay calculation for BD binaries from Umbreit et al (2005) (see Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These distributions were truncated at a = 10 au in order to better match what is known about wider binary systems. We also trialled the prediction from a triple-body decay calculation for BD binaries from Umbreit et al (2005) (see Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Also shown are the various model log a distributions used to simulate the VLM/BD binary population (see text). They are from Umbreit et al (2005) or are Gaussian distributions with peaks at 4 au and with various indicated widths (truncated for a > 10 au). The model distributions are normalised such that the binary frequency is 15 per cent for 2.6 < a < 10 au.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the binary fraction is an important prediction of brown dwarf formation scenarios, and, with other parameters, will eventually allow to discriminate between the various scenarios (Billères et al 2005;Umbreit et al 2005;Caballero 2007). In particular, Allen (2007) has analysed several high-resoution imaging surveys using a Bayesian algorithm.…”
Section: Naco Targetsmentioning
confidence: 99%
“…Several scenarios have been proposed to prevent a substellar core in a dense environment from accreting to stellar mass (e.g., dynamical interactions, Reipurth & Clarke 2001;Umbreit et al 2005; disk fragmentation, Goodwin & Whitworth 2007;Stamatellos et al 2007; or photoevaporation, Whitworth & Zinnecker 2004). Alternatively, brown dwarfs and free-floating planets (with masses below the deuterium-burning mass limit, 13M Jup ) could form in an isolated mode by direct collapse.…”
Section: Introductionmentioning
confidence: 99%